Requirements and selection decision of customers in Islamic and conventional banking environment - Haron, Sudin; Ahmad, Norafifah; Planisek, Sandra L. (Universiti Utara Malaysia, 1992)
Competition is the main challenge faced by commercial banks globally. They are not only competing just among themselves but also with other institutions within the financial industry. In Malaysia, the competition is becoming fiercer with the existence of banks which operate based on Islamic principles. To attract more customers both the bankers of conventional and Islamic banks should acquire information about factors which influence people in patronising their bank. This study investigates how Malaysian bank users select conventional banks, what services they want, also how they perceive Islamic banking. Results show that there are many similarities between Muslims and non-Muslims in their in their selection of banks and ulitization or services. A slight difference however, exists in their knowledge of Islamic banks.